2020
DOI: 10.1111/ffe.13317
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on creep‐fatigue behaviours of as‐received and service‐exposed turbine blades: Mechanism and life evaluation

Abstract: In the present study, both the as-received and the 600-h-serviced turbine blades were tested under the creep-fatigue loading. The results showed that the service-exposed blades exhibited a longer creep-fatigue life than the asreceived ones due to the refinement of grain size and the increasing of hardness during the service process. Micro structural characterization revealed that there was no directional coarsening or rafting of γ 0 precipitate after 600 h of service. Moreover, the as-received blades exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Generally, accelerated fatigue test was performed with the proper overstress and overtemperature to shorten the test period. In our previous study, [70][71][72][73] accelerated tests were performed on the full-scale turbine blade. The maximum stress at the blade bottom in service and accelerate test were 630 and 700 MPa, respectively.…”
Section: Test Matrixmentioning
confidence: 99%
“…Generally, accelerated fatigue test was performed with the proper overstress and overtemperature to shorten the test period. In our previous study, [70][71][72][73] accelerated tests were performed on the full-scale turbine blade. The maximum stress at the blade bottom in service and accelerate test were 630 and 700 MPa, respectively.…”
Section: Test Matrixmentioning
confidence: 99%
“…Based on the critical distance method, the creep‐fatigue life of complex structures was estimated with high prediction accuracy. In addition, in the creep‐fatigue test of the as‐received and the 600‐h‐serviced turbine blade, our team found that the life model considering the stress gradient effect has high prediction accuracy for the actual service structure 11 . Li et al 12 proposed a new double slope method to calculate the critical distance for notched plate models with different materials.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, in the creepfatigue test of the as-received and the 600-h-serviced turbine blade, our team found that the life model considering the stress gradient effect has high prediction accuracy for the actual service structure. 11 Li et al 12 proposed a new double slope method to calculate the critical distance for notched plate models with different materials. The geometric factor and stress factor were defined considering the geometric characteristics of the notch and the influence of external load.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extended Y-W model ignores the effect of load interaction under the multilevel loading condition. 32,33 2.2 | The modified Y-W models…”
Section: Introductionmentioning
confidence: 99%